PENGAMBILAN KEPUTUSAN STRATEGIS BERBASIS DATA DALAM ORGANISASI PENDIDIKAN: TANTANGAN DAN STRATEGI IMPLEMENTASI DI ERA TRANSFORMASI DIGITAL - Jon Roi Tua Purba; Adrianus T. H. Mahulae; Deasy H. P. Manurung; Lustani Samosir; Arip Surpi Sitompul (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Digital transformation has driven a paradigm shift in the management of educational organizations, particularly in decision-making processes that increasingly emphasize the use of data as the basis for policy development. This article aims to analyze the concept, supporting factors, inhibiting factors, and implementation strategies of Data-Driven Decision Making (DDDM) in educational organizations during the era of digital transformation. The study employed a descriptive-qualitative literature review approach. Data were collected from Google Scholar, Garuda, and the Directory of Open Access Journals (DOAJ), covering publications from 2016 to 2026. Out of 85 identified articles, 28 met the inclusion criteria and were analyzed using content analysis techniques. The findings indicate that DDDM plays a significant role in enhancing educational management effectiveness through the utilization of objective and evidence-based data. Successful implementation is influenced by data quality, data literacy among human resources, visionary leadership, information technology support, and an organizational culture that promotes data utilization. Conversely, low levels of data literacy, limited technological infrastructure, resistance to change, and weak data-use culture constitute major barriers to implementation. The study concludes that effective DDDM requires the integration of data, technology, leadership, human resources, and organizational culture to achieve educational governance that is effective, adaptive, and sustainable. Keywords: Data-Driven Decision Making, data-based decision making, digital transformation, educational management, educational organizations.   Abstrak: Transformasi digital telah mendorong perubahan paradigma pengelolaan organisasi pendidikan, khususnya dalam proses pengambilan keputusan yang semakin menekankan pemanfaatan data sebagai dasar kebijakan. Artikel ini bertujuan untuk menganalisis konsep, faktor pendukung, faktor penghambat, serta strategi implementasi Data-Driven Decision Making (DDDM) dalam organisasi pendidikan di era transformasi digital. Penelitian menggunakan metode literature review dengan pendekatan deskriptif-kualitatif. Sumber data diperoleh dari Google Scholar, Garuda, dan Directory of Open Access Journals (DOAJ) dengan rentang publikasi tahun 2016–2026. Dari 85 artikel yang ditemukan, sebanyak 28 artikel memenuhi kriteria inklusi dan dianalisis menggunakan teknik analisis isi (content analysis). Hasil kajian menunjukkan bahwa DDDM berperan penting dalam meningkatkan efektivitas manajemen pendidikan melalui pemanfaatan data yang objektif dan berbasis bukti. Keberhasilan implementasinya dipengaruhi oleh kualitas data, literasi data sumber daya manusia, kepemimpinan yang visioner, dukungan teknologi informasi, dan budaya organisasi yang mendukung penggunaan data. Sebaliknya, rendahnya literasi data, keterbatasan infrastruktur teknologi, resistensi terhadap perubahan, serta lemahnya budaya penggunaan data menjadi hambatan utama. Kajian ini menyimpulkan bahwa implementasi DDDM memerlukan integrasi antara data, teknologi, kepemimpinan, sumber daya manusia, dan budaya organisasi untuk mewujudkan tata kelola pendidikan yang efektif, adaptif, dan berkelanjutan. Kata kunci: Data-Driven Decision Making, pengambilan keputusan berbasis data, transformasi digital, manajemen pendidikan, organisasi pendidikan.